Analysis of the world experience on the approaches to the definition of disability: on the way to reforming the system of medical and social expertise - I.S. Borysova (Medičnì Perspektivi)
The Ukrainian system of medical and social expertise needs to revise its conceptual and methodological foundations in accordance with the realities of the current development of social sciences in the world and demand of the state regarding the modern understanding of disability. The purpose of the study was to analyze international experience and legislation on policy towards persons with disabilities and systematic approaches to the criteria of violation of functioning and the possibilities of determining the status of "person with disabilities" using the basic principles of the International Classification of Functioning (ICF), Impairment and Health to create optimal approaches to determining the criteria for disability in Ukraine. The study was based on the analysis of available scientific literature and legislative documents of developed countries on the understanding of the concept of "person with a disability". The scientometric databases used were Scopus, Web of Science, Google Scholar, and MedLine. Data from the official websites of the Political Department of the European Parliament, WHO, the United Nations, UNICEF, the World Bank. Аccording to the results of the study, it is determined that a single state body is responsible for determining the status of a person with a disability in sustainable development countries using a multidisciplinary approach. The author identifies 3 main components that most developed countries assess when determining disability: economic, medical and social. At the same time, the main criterion is decreased performance. It has been established that since 2022, Spain has completely switched to the criteria of the International Classification of Functioning in determining the signs of disability, basing the severity of a person's condition as a degree of disability on a percentage decrease in the person's functioning. Some European countries use selective categories of the ICF.